LncRNA and transcriptomic analysis of fetal membrane reveal potential targets involved in oligohydramnios - Ou, Yu-hua (BMC Med Genomics, 2020)
BACKGROUND: The multiple causes of oligohydramnios make it challenging to study. Long noncoding RNAs (lncRNAs) are sets of RNAs that have been proven to function in multiple biological processes. The purpose of this study is to study expression level and possible role of lncRNAs in oligohydramnios. METHODS: In this study, total RNA was isolated from fetal membranes resected from oligohydramnios pregnant women (OP) and normal amount of amniotic fluid pregnant women (Normal). LncRNA microarray was used to analyze the differentially expressed lncRNAs and mRNAs. Kyoto Encyclopedia of Genes and Genomes (KEGG) was used to analyze the main enrichment pathways of differentially expressed mRNAs. Real-time quantitative PCR (qPCR) was used to validate the lncRNA expression level. RESULTS: LncRNA microarray analysis revealed that a total of 801 lncRNAs and 367 mRNAs were differentially expressed in OP; in these results, 638 lncRNAs and 189 mRNAs were upregulated, and 163 lncRNAs and 178 mRNAs were downregulated. Of the lncRNAs, 566 were intergenic lncRNAs, 351 were intronic antisense lncRNAs, and 300 were natural antisense lncRNAs. The differentially expressed lncRNAs were primarily located in chromosomes 2, 1, and 11. KEGG enrichment pathways revealed that the differentially expressed mRNAs were enriched in focal adhesion as well as in the signaling pathways of Ras, tumor necrosis factor (TNF), estrogen, and chemokine. The qPCR results confirmed that LINC00515 and RP11-388P9.2 were upregulated in OP. Furthermore, the constructed lncRNA–miRNA–mRNA regulatory network revealed tenascin R (TNR), cystic fibrosis transmembrane conductance regulator (CFTR), ATP-binding cassette sub-family A member 12 (ABCA12), and collagen 9A2 (COL9A2) as the candidate targets of LINC00515 and RP11-388P9.2. CONCLUSIONS: In summary, we revealed the profiles of lncRNA and mRNA in OP. These results might offer potential targets for biological prevention for pregnant women with oligohydramnios detected before delivery and provided a reliable basis for clinical biological treatment in OP.